The Most Eloquent Grammatically in Abi Hayyan’s Al-Bahr Al-Muheet - Nama, mohammed Sabar (Journal of Tikrit University for Humanities, 2023)
The grammatical precision is contingent upon the underlying verbal context, sometimes referred to as the verbal event. The academics’ ijtihad was not only reliant on the verbal expressions of the Arabs, but rather required a comprehensive examination of several aspects of the matter in question in order to get a clear understanding. For instance, it can be observed that the sentence "Zaid came" consists of a verb and a subject when analyzed in terms of inflection. However, when the sentence is expressed as "Zaid came," it exhibits two grammatical forms in terms of inflection: the first being a subject and a predicate, and the second being a subject followed by a delayed verb. Both of these forms are considered acceptable within the framework of Arabic grammar. The first sentence stands out as the most eloquent grammatically due to its lack of affectation. It adheres to the well-established grammatical rule that inflection should be placed on the main sentence. However, this does not exclude the possibility of inflection occurring on the participle. Nevertheless, the most eloquent and optimal approach is to place the inflection on the element that has been mentioned.